THE IMPACT OF DIGITAL TRANSFORMATION ON CONSUMER BEHAVIOR AND MARKETING STRATEGIES - Haudi Haudi (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
The rapid pace of digital transformation has revolutionized consumer behavior, reshaping the landscape in which businesses operate. This study delves into the multifaceted impact of digital transformation on consumer behavior and the consequential adjustments required in marketing strategies. The research explores how digital transformation influences decision-making processes, brand interactions, and overall consumer experiences, analyzing the dynamic interplay between technological advancements and evolving consumer expectations. Additionally, it investigates the adaptive strategies marketers employ to harness the potential of digital transformation, leveraging tools such as data analytics, artificial Intelligence, and omnichannel approaches. The findings contribute valuable insights for businesses navigating the digital era, guiding them in crafting effective marketing strategies that align with the transformed consumer landscape.